2018
DOI: 10.1590/2177-6709.23.1.108-117.sar
|View full text |Cite
|
Sign up to set email alerts
|

The T-loop in details

Abstract: Introduction: The T-loop as designed by Burstone is a space closure spring used in the rational application of orthodontic biomechanics. Despite the diversity of studies, there is still no consensus on the optimal parametric characteristics for its conformation. Objective: This study aimed at reviewing the literature on the force systems released by different conformations of the T-loop, according to the type of anchorage and the main characteristics and factors that influence them. Results: Comparing the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…The analysis of the four retraction techniques evaluated in this study revealed interesting results for understanding the behavior of the strains generated during the correction of malocclusions where orthodontic retraction of anterior teeth is indicated. This procedure is greatly studied in the orthodontic literature, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]22,23 however none of the previous investigations made a linear comparison among the application of these four mechanics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The analysis of the four retraction techniques evaluated in this study revealed interesting results for understanding the behavior of the strains generated during the correction of malocclusions where orthodontic retraction of anterior teeth is indicated. This procedure is greatly studied in the orthodontic literature, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]22,23 however none of the previous investigations made a linear comparison among the application of these four mechanics.…”
Section: Discussionmentioning
confidence: 99%
“…30 When intending to create a final force vector for tooth body movement, the retraction force applied to the anteroinferior teeth was complemented by an additional vertical control, to generate an opposite intrusion moment of force, which attempted to annul the extrusion moment of force caused by the resistance to the retraction in relation to the tooth resistance center, suggesting a final resultant force without intrusion or extrusion of the anterior segment (Fig 5). 4,5,[10][11][12][13][14][15] For this reason, in the sliding mechanics long hooks were added to the archwire to activate the system close to the tooth resistance center [6][7][8] . For the mechanics applying loops (teardrop loop spring and T-loop spring), a Gable bend was incorporated for each respective loop.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations